Water Hyacinth (Eichhorniacrassipes) Ethanolic Extract Anti Platelet Activity - Nursidika, Perdina (KnE Life Sciences, 2021)
Cardiovascular diseases (CVDs) are a group of disorders of the heart and blood vessels. CVDs are responsible for 37% of deaths in Indonesia. Thrombosis is the main factor causing blood vessel clost in CVDs. Blood vessel clots then affect narrowed blood vessel. This causes strokes. The aim of this study is to determine the antithrombotic effect of water hyacinth ethanolic extract, the effective dose, and the potential to become anticoagulant agent. The water hyacinth was extracted by ethanol 96%. The extract was tested on five groups of mice, each group containing five mice. Each group was tested for fourteen days. Group I and II are fed by extract suspension with varied dose 1 mg/BW and 2 mg/BW. Group III is fed by warfarin as standard. Group IV and V are the positive and negative group, the mice were fed by NaCMC. On the 7th and 14th days, prothrombin time (PT) and activated partial thromboplastin time (aPTT) were conducted. The plasma of group 1-IV mixed with adenosine diphosphate (ADP) as inducer, except plasma of group V used for negative control, did not mixed with ADP. Data analysed by ANOVA and LSD to obtain effective dose. The results showed the difference between PTT and aPTT among the tested groups. Group I and II showed prolonged PT which is 22 and 32 seconds respectively. The control positive showed PT 9.48 seconds on day 7th and 8.22 seconds on day 14th. LSD analysis showed that there is the significant difference between positive control and the other groups. It showed platelet aggregation performed due to the addition of ADP as inducer. There was a significant difference between dose 2 and the negative control group, and there is no significant difference of dose 1. In conclusion, water hyacinth has the antithrombotic activity, the effective dose is 1 mg/BW, and it potential to further developed as anticoagulant agent. Keywords: antiplatelet, cardiovascular diseases, water hyacinth.